Group Discussion Method to Improve Learning Outcomes of Grade VII Students in Fiqh Learning: Action Research at MTs Al-Insan - Muhtar (MANDAILING GLOBAL EDUKASIA, 2025)
The problem in this study is whether the application of the group discussion method can improve the learning outcomes of Class VII students in the Fiqh Subject in the 2021-2022 Academic Year at MTs AL-Insan Cilegon Lombok Timur. This study uses a classroom action research (CAR) design. With class VII research subjects totaling 9 male students. Using an instrument in the form of a learning outcome evaluation test. This classroom action research design was carried out in 2 cycles with each cycle going through four stages, namely: (1) planning, (2) implementation of actions, (3) observation, and (4) reflection. The results of the study in cycle I showed that students and teachers in learning activities for the average level were classical completion of 25.% and individual absorption of 50%. In cycle II it increased to classical completion of 100% and individual absorption of 83%, and for the assessment of student observations in cycle I, namely 50 increased to cycle II to 83, for the assessment of teacher observations in cycle I 100%, cycle II 100%. Based on the analysis of the results of the first cycle test, 2 out of 9 students completed, 25% completed classically and their individual absorption capacity was 50%, while in the second cycle, 9 out of 9 students completed, 100% completed classically and their classical absorption capacity was 83%. Based on the results of the study, it can be concluded that the application of the group discussion method can improve student learning outcomes in class VII MTs AL-INSAN CILEGON Sakra in fiqh learning.